2021
DOI: 10.1111/ppl.13416
|View full text |Cite
|
Sign up to set email alerts
|

Plant aquaporins: A frontward to make crop plants drought resistant

Abstract: Drought stress alters gene expression and causes cellular damage in crop plants. Drought inhibits photosynthesis by reducing the content and the activity of the photosynthetic carbon reduction cycle, ultimately decreasing the crop yield. The role of aquaporins (AQP) in improving the growth and adaptation of crop plants under drought stress is of importance. AQP form channels and control water transport in and out of the cells and are associated with drought tolerance mechanisms. The current review addresses: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 165 publications
(194 reference statements)
0
18
0
1
Order By: Relevance
“…It was reported that ABA increases the activity of aquaporins and improves root hydraulic conductivity [ 44 ]. The activity of aquaporins is also regulated by gibberellins (GAs), CKs, methyl jasmonate (MeJA), and AUXs at transcriptional and post-transcriptional levels ([ 45 ] and references therein). The anisohydric strategy is beneficial under mild to moderate drought conditions but may be a risk under severe and long-term stress, which may cause hydraulic failure and severe dehydration [ 20 ].…”
Section: Plant Responses To Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ABA increases the activity of aquaporins and improves root hydraulic conductivity [ 44 ]. The activity of aquaporins is also regulated by gibberellins (GAs), CKs, methyl jasmonate (MeJA), and AUXs at transcriptional and post-transcriptional levels ([ 45 ] and references therein). The anisohydric strategy is beneficial under mild to moderate drought conditions but may be a risk under severe and long-term stress, which may cause hydraulic failure and severe dehydration [ 20 ].…”
Section: Plant Responses To Droughtmentioning
confidence: 99%
“…Thanks to the efficient antioxidative system, plants can keep ROS at non-toxic levels, and these molecules are thought to act as signals for activation of stress defense responses [ 45 , 54 ]. It was also evidenced that NADPH oxidase localized in apoplastic fluid is involved in ROS production for integrating signaling networks involved in stress response processes.…”
Section: Plant Responses To Droughtmentioning
confidence: 99%
“…Drought is the major stress that alters physiological, biochemical, and molecular processes in plants [11,12,98,99]. The plants grown in arid and semi-arid regions will face more intense and longer periods of drought [100].…”
Section: Melatonin Under Drought Stressmentioning
confidence: 99%
“…The plants grown in arid and semi-arid regions will face more intense and longer periods of drought [100]. The urgent need of the hour in these changing environmental conditions is to promote adaptive agricultural strategies because numerous levels of sensitivity to water stress are shown by different organs [12,101]. Cucumis sativus exposed to melatonin has a higher rate of germination of seeds and root growth when grown in PEG-stressed conditions [36] and reduced drought-promoted leaf senescence in Agrostis [68].…”
Section: Melatonin Under Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation